Studi deskriptif: Gambaran perilaku merokok di Polresta Magelang - Yuliadi, Iwan; Priyanto, Sigit; wardani, septi; Priyo, Priyo (Universitas Muhammadiyah Magelang, 2025)
Background: Smoking is an irritating and unhealthy habit. Smoking habits and views about smoking characterize the behavior and intensity of smoking. The Magelang Police Department has a 51.8% bad smoking rate and a 48.2% good smoking rate. Purpose: The purpose of this study is to identify respondents' smoking behavior and degree of smoking while working for the Magelang Police. Method: The research strategy was quantitative (non experimental), with a descriptive research design. The sample technique used was non- probability sampling with random sampling. Data on examination outcomes were collected from May to June 2024. This study included 251 respondents. Result: According to the study's findings, the majority of respondents had poor smoking habits and smoke heavily. Conclusion: The research findings suggest that the longer and more frequently someone smokes, the worse the picture of their smoking behavior becomes. Keywords: smoking; smoking behavior; level of smoking